Effect of virtual learning on delivering the education as part of the sustainable development goals in Qatar. (December 2020) - Al-Jaber, Maryam A.; Al-Ghamdi, Sami G.
Abstract: In the recently identified pandemic of COVID-19, most countries have stopped their work, industrial activities, businesses and education activities. This pandemic also had a great impact on energy and environment research, which is a vital component in the transition to sustainable development. In response to this pandemic, Qatar had to stop all kinds of on-site education activities and shifted to virtual learning techniques (or distance learning). Using distant learning has a potential impact on the quality of education and research activities, especially energy and environment research. So, to assess the effectiveness of virtual learning in this pandemic time in Qatar, a structured survey is conducted for university students and staff to assess their perception about distant learning. The survey revealed that virtual learning overall had a positive impact, but it can affect the quality and the progress of education in the country.